Nitrogen-Rich Perylene Nanosheet Enhanced Bismaleimide Resin - Peng, Yuting; Luo, Yan; Wu, Qian; Huang, Yun; Yang, Long (Journal of Research Updates in Polymer Science, 2023)
The low toughness of bismaleimide resin (BMI) hinders its application in the aerospace field. In order to improve the strength and toughness of BMI resin simultaneously, this study proposes to introduce perylene-dicyandiamide (P-DCD) nanosheets with an ultra-s rigid conjugated planar structure into the polymer matrix of bismaleimide resin through hydrogen bonding and cross-linking to construct modified composites. The research results showed that the modified cured composites exhibited excellent mechanical properties, with a significant increase in impact strength of 135.8%, flexural strength and flexural modulus of 87.1% and 44.6%, respectively. The thermal properties of the resin were maintained before and after modification, with the glass transition temperature (Tg) of 284.0 ˚C and decomposition temperature > 520 ˚C. Meanwhile, the strengthening and toughening mechanism of the bismaleimide-based system modified by additive P-DCD were also explored. The results showed that the functional group of dicyandiamide in nanosheets and the hydrogen bonding effect in P-DCD synergically increased the cross-linking network and compatibility between P-DCD and the matrix resin.